58. A CASE OF SYNCHRONOUS PLEOMORPHIC ADENOMAS ARISING IN THE PAROTID AND AN INTRAPAROTID LYMPH NODE. (February 2015) - Thompson, K.; Smith, A.; Perry-Keene, J.; Grieve, D.; Leeb, G.
Abstract : Pleomorphic adenoma is a benign salivary gland tumour that commonly arises in the parotid gland. There are very few reported cases of pleomorphic adenomas arising in lymph nodes. We present an interesting and rare case of this benign entity occurring synchronously in the parotid and an intraparotid lymph node of a 31 year old woman. A brief review of the literature will be included.